DAMPAK KENAIKAN TARIF CUKAI DAN PENGENAAN PAJAK ROKOK ELEKTRIK PADA PELAKU USAHA ROKOK ELEKTRIK DI KOTA KUPANG - Angela Merici Minggu; Varel Julian Ballo; Christian Daniel Manu (Universitas Merdeka Madiun, 2025)
Based on the Regulation of the Minister of Finance number 143/PMK.010/2023, cigarette excise is a state levy imposed on cigarettes. Cigarette tax is a state levy on cigarette tax collected directly by the central government. The object of cigarette tax is tobacco products including cigarettes, cigars, leaf cigarettes, and other forms of cigarettes imposed on cigarettes. Then, the subject of cigarette tax itself is cigarette consumers, with taxpayers being cigarette factory entrepreneurs/producers and cigarette importers who have an Exciseable Goods Entrepreneur Identification Number (NPPBKC) permit. This study aims to describe the impacts caused by the increase in excise rates and the imposition of taxes on electronic cigarettes in Kupang City. The population used in this study were business owners and employees of Vape Shop XX Kupang. The sample of this study consisted of 3 people consisting of the business owner and two employees. The data collection technique used in this study came from primary data or data obtained directly through interviews with business owners and employees of Vape Shop XX Kupang. This study also uses secondary data, namely data on the percentage of smokers in Kupang City based on the 2013 and 2018, and excise rates based on Minister of Finance Regulation No. 192/PMK.010/2022. The results of the study show that the increase in excise rates and the imposition of taxes on electronic cigarettes have an impact on the understanding of excise and taxes, public consumption, electronic cigarette trade, and the response of the Kupang City community.